Anthropometric Parameterisation of a Spherical Scatterer ITD Model with Arbitrary Ear Angles - Gamper, Hannes; Thomas, Mark; Tashev, Ivan (Proc. IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA), 2015)
Accurate modelling of the interaural time difference (ITD) is crucial for rendering localised sound. Parametric models allow personalising ITDs using anthropometrics. However, the mapping between anthropometric features and model parameters is not straightforward. Here, we propose deriving personalised ITD model parameters from a sphere fitted to a 3-D head scan. The proposed ITD personalisation is evaluated on an HRTF database containing 181 subjects, for a simple spherical ITD model as well as a frequency and elevation-dependent spherical scatterer model with arbitrary ear angles.